Subsea pipeline design, analysis, and installation - Bai, Qiang (Gulf Professional Publishing, 2014)
"Subsea pipelines are used for a number of purposes in the development of subsea hydrocarbon resources as shown in Figure 1.1. A pipeline system can be a single-pipe pipeline system, pipe-in-pipe or bundled system. Normally, the term of subsea flow-lines is used to describe the subsea pipelines carrying oil and gas products from the wellhead to the riser base; the riser is connected to the processing facilities (e.g. a platform or a FPSO). The subsea pipelines from the processing facilities to shore are called export pipelines, while the subsea pipelines from the platform to subsea equipment used to transfer water or chemical inhibiters are called water injection or chemical flow-lines"--